2021
DOI: 10.14814/phy2.15129
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cardiac loading on a novel metric of left ventricular diastolic function in healthy middle‐aged adults: Systolic–diastolic coupling

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…Previous studies from our group have shown that, like LV relaxation, S-D coupling declines with age, and S-D coupling is preload independent, unlike early diastolic recoil velocity (e'). 13,24 The present study demonstrates that in healthy adults the link between fitness and S-D coupling appears primarily driven by age. The fitness of most adults is "cardiac-limited" as the stroke volume and heart rate cannot increase indefinitely to support higher peak V Ȯ2 .…”
Section: Impaired Myocardial Mechanics and Exercise Intolerance In Hcmmentioning
confidence: 51%
See 1 more Smart Citation
“…Previous studies from our group have shown that, like LV relaxation, S-D coupling declines with age, and S-D coupling is preload independent, unlike early diastolic recoil velocity (e'). 13,24 The present study demonstrates that in healthy adults the link between fitness and S-D coupling appears primarily driven by age. The fitness of most adults is "cardiac-limited" as the stroke volume and heart rate cannot increase indefinitely to support higher peak V Ȯ2 .…”
Section: Impaired Myocardial Mechanics and Exercise Intolerance In Hcmmentioning
confidence: 51%
“…An advantage of S-D coupling is that it is a relative marker and independent of heart size. 24 Future studies characterizing S-D coupling are needed to determine the effects of body size. Fourth, the non-invasive nature of this study limits our ability to assess important parameters of diastolic function, including LV relaxation, LV stiffness, and LV filling pressures.…”
Section: Limitationsmentioning
confidence: 99%
“…Assessing mechanical dispersion, myocardial work, isovolumetric relaxation and systolic-diastolic coupling can provide complementary information on the global and regional LV function and performance in healthy subjects. All of these parameters have demonstrated clinical value [1,[11][12][13][14][15][16][17][18][19][20]27,[32][33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…A close relationship between systolic contraction and relaxation (systolic-diastolic coupling) influences global LV performance. E VTI /S VTI , a measure of systolic-diastolic coupling, describes the ratio of early diastolic recoil to systolic excursion, as explained by MacNamara et al [27] with the spring model of LV longitudinal motion. In other words, it shows which part of the systolic movement of the LV base toward the apex is compensated during early diastole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation